Ventral hernia and patient experience of an elastic girdle. Issue 7 (5th December 2014) - Strigård, Karin; Stark, Birgit; Bogren, Agneta; Gunnarsson, Ulf
Abstract: Background: Abdominal girdles are used to prevent hernia and to facilitate the in‐growth of mesh following ventral hernia surgery or instead of surgery. Scientific evidence supporting the use of girdle, including patient experience, is lacking. The aim was to investigate patient experience of wearing an elastic girdle in terms of support and tolerability. Methods: A trans‐sectional study with quantitative onset was performed. Telephone interviews following a strict protocol were performed 2 years after girdle prescription. Of the 89 eligible patients, 67 completed the interview. The questionnaire constituted 13 questions. Results: Of the 52 women and 15 men, two thirds had ventral hernia surgery. Patients over 70 years more often used girdle as a substitute for surgery. Most patients (64%) were satisfied with the girdle and 94% used it as prescribed. Five out of 53 who used girdles preoperatively stated no improvement in their inconvenience. Almost all patients (97%) had some problem with the girdle. Conclusion: In this first study on patient experience, nearly all patients used it as prescribed and subjective benefit was achieved even though side effects were present in most cases. Individual fitting and improved information about when and how to use the girdle is important for patient comfort and optimal function. This study attended patient experience of negative side effects from wearing a girdle. Improvement may be reached concerning comfort from the patients' perspective. The importance of both written and oral information has been revealed.